Consumer’s intention to purchase towards green technology- a case study in automatize industry in Kuala Lumpur Malaysia - Afroz, Rafia (s.n, 2013)
This paper investigates how individual values and attitudes in a developing country like Malaysia influence purchase intention of an environmental friendly car using the motivation Theory of Reasoned Action (TRA). It also investigates how value may affect attitudes towards environmentally responsible purchase intention. The study analyzed data collected from 200 household asking their observation relating their value sets, attitudes and purchase intention of environment friendly car using the Structural Equation Modeling (SEM) technique